Guest Editorial: On the Potential Role of Psi in an Expanded Science of the Physical, Experiential and Spiritual - Tart, Charles (Journal of Scientific Exploration, 2019)
Note: This paper is an experiment for me, so there may be rough spots. Its basic goal is to share my excitement about possibilities for parapsychological applications to help investigate reality, to hopefully stimulate readers who will advance these ideas…I’m relatively retired now. It was originally scripted as an invited address. I’m a good speaker, and it’s easy for me to share possibilities by the way my voice and gestures communicate my excitement, and the controlled pace of a lecture lets me build the right atmosphere. Too, when I’m a well-known scientist and colleague to the audience, I can deepen rapport by being relatively informal and personal while outlining the basic science. But converting this to a journal article eliminates much of the above advantages inherent in speaking, and a journal article should more formally demonstrate some of the scientific roots of my proposals, especially to younger investigators who don’t know my previous work. So the experiment I’m trying here is to stick close to the somewhat personal, informal, enthusiasm-conveying tone of a lecture but demonstrate its scientific roots with extensive endnotes. I invite you to read just the text, pick up on the feelings, put questions and criticism aside for the time being. “Take the trip” with me, while skipping the endnotes (I know you’ll peek at the first few anyway). Then if you have picked up enough enthusiasm to want to go deeper, go back through reading the endnotes to get the references, methodological deepenings, questionings, etc. And then…maybe you’ll be one of those who advances our fields along these lines! In 2018 I was honored by being asked to give an invited lecture at the annual meeting of the Parapsychological Association. What would I talk about? I think of my primary professional identity as being that of a transpersonal psychologist, interested in the wider aspects of the human mind–actually I'm interested in too many things, but that's how I attempt to focus–but parapsychology has usually taken up about a third of my professional time. The problems posed by the existence of psi are especially interesting, and psi phenomena their implications are very important for people in general[i], as well as scientists. Also, since it is still largely a taboo topic in science, for various irrational reasons, parapsychology has remained a very tiny scientific field, with very few people working in it, even part-time, and very few resources available for wide scale experimentation. So my first thought of what to talk about in my lecture time was that in the half-century+ I’ve worked in parapsychology, I've seen a lot of promising, initial developments that didn't really get followed up adequately, so perhaps I could devote my hour to discussing methodological problems and promising leads that had slipped between the cracks? I am very empirically oriented. At least that's what I discipline myself to be: what are the observable facts in a particular area? That’s the primary thing, indeed the essential thing to work from. I say discipline myself to be that way, because most of my life I've been what I call, in a term I coined, a thoughtaholic. I love clever thoughts! If I were to go to something like an Alcoholics Anonymous meeting and was asked what my drug of choice was, I would say something like "Ideas! Concepts! Theories! They get me so high! I get so attached to them!" Thinking about things and coming up with what seem to be insights about them has been a major quality of my consciousness since I was a child. That's why science is a wonderful personal discipline for me. If I had to characterize essential science very simply, I would say we’re curious and want to find out things. We create clever ideas as to why things are the way they are, but must constantly ask if our clever theories fit the current observable data and predict future, observable data? If they don't fit the observable data, or make any testable predictions, the theory is a nice idea, but it's got to be modified or dropped in favor of something more adequate if it’s to be part of essential science. Back to the drawing board! Data is always more important, more basic than theory! As important as accounting for observable facts is, I didn't want to give a mainly negative talk about methodology and problems we haven't solved, things that didn't work. Yes, there are real problems, but we can potentially solve them! Negative focus would also tie in too well with the fact that the field of parapsychology has been stuck in the more proof, more proof, … more proof ad infinitum stage, ignoring the fact that most of the opposition to its findings is irrational, stemming from common human shortcomings of people rather than their scientific skills. To the contrary, I believe that parapsychology now has the potential to build investigative tools that will be central to an expanded scientific and human/spiritual understanding of the mind. What I’ve learned working with parapsychology, altered states of consciousness, transpersonal psychology and related fields have been a personal inspiration to me throughout my life, and I want to share that inspiration! [i] I will use endnotes to insert references to more detail, methodological points, and suggestions for deeper exploration, but, as I explain later in the text, the important overall message of this essay can best be grasped, with, I hope, enthusiasm, by saving the endnotes for more detailed reading later. At this specific point, I simply refer to my most recent and comprehensive book on psi and consciousness (The End of Materialism: How Evidence of the Paranormal is Bringing Science and Spirit Together) (C. Tart, 2009) where I have indicated a number of reasons psi is important for any intelligent person’s worldview. The hardback is now out of print, but it’s available in paperback as The Secret Science of the Soul: How Evidence of the Paranormal is Bringing Science and Spirit Together (Charles Tart, 2017). I expect the High Priests of the Church of Absolute Materialism to show up any day to take my white lab coat back for daring to use a word like soul… ;-)